Bacterial flora and the epidemiology of staphylococcus aureus in the nose among patients with symptomatic nasal septal perforations. (2nd June 2016) - Hulterström, Anna Karin; Sellin, Mats; Monsen, Tor; Widerström, Micael; Gurram, Bharath Kumar; Berggren, Diana
Abstract: Conclusions Patients with symptomatic perforations of the nasal septum had a high prevalence of S. aureus in the nasal mucosa. Pulsed field gel electrophoresis (PFGE) analysis revealed a high genetic heterogeneity of S. aureus among both patients and controls. This indicates that presence of different strains of S. aureus can maintain a chronic inflammation in symptomatic nasal septal perforations.Objective The purpose of this study was to investigate the microbial flora around nasal septal perforations in patients having severe symptoms regarding bleeding, obstruction, and crustation associated with their perforation.Methods Twenty-five patients with untreated symptomatic nasal septal perforations were included. For culture, swabs around the perforations were collected. Bacteria were identified with standard laboratory techniques including a MALDI-TOF mass spectrometer. Epidemiological analysis was done using PFGE protocols. Bacteriological data were compared with data from a healthy control group.Results Staphylococcus aureus was present in the mucosa surrounding the nasal perforation significantly more often ( p < 0.0001) in the patients (88%) compared to a control group (13%). Corynebacterium spp. and Propionibacterium spp. were significantly more frequently identified in the control group. The PFGE analysis of S. aureus strains revealed a high genetic heterogeneity and no specific S. aureus genotypes were associated with septal perforation.